ChemInform Abstract: Hierarchical Zeolites Overcome All Obstacles: Next Stop Industrial Implementation. Issue 44 (14th October 2013) - Verboekend, Danny; Mitchell, Sharon; Perez‐Ramirez, Javier
Abstract Review: 38 refs.